DERRAMAMENTO DE ÓLEO NO MAR E IMPLICAÇÕES TÓXICAS DA EXPOSIÇÃO AOS COMPOSTOS QUÍMICOS DO PETRÓLEO: OIL SPILL IN THE SEA AND TOXIC IMPLICATIONS OF EXPOSURE TO PETROLEUM CHEMICAL (Revista Contexto & Saúde, 2022)
Petroleum is a fossil fuel composed mainly of polycyclic aromatic hydrocarbons whose persistent toxic and bioaccumulative organic pollutants. Recently, the oil spill that occurred on the coast of Northeast Brazil was a major environmental disaster and caused an impact on the marine and terrestrial environment for plants, animals and humans. The present study is a narrative review on cases of oil spills and toxic effects on the environment and human health. Databases were used to search for national and international articles, in addition to a monograph, dissertation, technical notes and news about the topic to compose this review. Important environmental accidents resulting from the oil spill at sea and / or exposure to the chemical constituents of petroleum promoted environmental damage (blocking the systems of filtering animals, reducing the photosynthetic action of plant species, emitting polluting gases in the air and decreasing the natural defense soil), and human health (carcinogenicity, hematoxity, neurotoxicity and psychosocial damage). The most common way of contamination of the population caused by oil is through the respiratory tract, which can also occur through ingestion, with risks still unclear regarding the consumption of contaminated food. Alternatives for the use of the large amount of oil taken from the beaches of Northeastern Brazil have been developed in the study centers of the affected regions. Studies are needed to measure the long-term environmental and human health impact and strategies to accelerate the biodegradation of this contaminating material.
Keywords: Petroleum; Atlantic Ocean; Ocean; Toxicity